Pemanfaatan Aplikasi Quizziz Sebagai Media Pembelajaran Berbasis Problem Based Learning Untuk Meningkatkan Keaktifan Siswa Kelas 8 Aisyah Di Smpit Insan Permata: Penelitian - Lifa Rosiana Putri; Agus Purnomo (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
This study aims to determine the effectiveness of using the Quizziz application as a learning medium based on Problem-Based Learning (PBL) in increasing student engagement in grade 8 Aisyah at SMPIT Insan Permata in the Social Studies subject. The background of this study stems from the low involvement of students during learning, which remains passive and lacks motivation. This research uses a quantitative-experimental approach with a static group post-test only design, involving 30 students as research respondents. The treatment provided was the implementation of the Problem-Based Learning (PBL) model supported by the Quizziz media, while learning outcomes were obtained through a post-test and analyzed based on a minimum mastery criterion (KKM) of 80. The results showed that 94% of students achieved scores above the KKM, consisting of 52% in the very proficient category, 42% proficient, and 6% of students requiring additional guidance. The implementation of the PBL model with the assistance of Quizizz has been proven effective in increasing student engagement, motivation, and learning outcomes, as interactive features such as gamification, immediate feedback, and real-time scores can create a more engaging, participatory, and meaningful learning process.